2012
DOI: 10.1021/nn301639j
|View full text |Cite
|
Sign up to set email alerts
|

Self-Encapsulated Doping of n-Type Graphene Transistors with Extended Air Stability

Abstract: This paper presents an innovative approach to fabricating controllable n-type doping graphene transistors with extended air stability by using self-encapsulated doping layers of titanium suboxide (TiOx) thin films, which are an amorphous phase of crystalline TiO(2) and can be solution processed. The nonstoichiometry TiOx thin films consisting of a large number of oxygen vacancies exhibit several unique functions simultaneously in the n-type doping of graphene as an efficient electron-donating agent, an effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
95
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 36 publications
7
95
0
Order By: Relevance
“…19 As shown in Figure 2, after pre-H 2 O treatment and ALD-Al 2 O 3 growth, the 2D peak of graphene shifted down from 2690 to 2685 cm −1 , due to the effect of the Fermi level shift on the photon frequencies as a result of n-type doping of graphene. 19,22 In addition, the full width at half-maximum (fwhm) values of the 2D peak shifted up from 43 to 47 cm −1 . Both of these Raman spectroscopy results including the 2D peak left-shifting and blunting were consistent with those observed in typical n-type doping of graphene.…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…19 As shown in Figure 2, after pre-H 2 O treatment and ALD-Al 2 O 3 growth, the 2D peak of graphene shifted down from 2690 to 2685 cm −1 , due to the effect of the Fermi level shift on the photon frequencies as a result of n-type doping of graphene. 19,22 In addition, the full width at half-maximum (fwhm) values of the 2D peak shifted up from 43 to 47 cm −1 . Both of these Raman spectroscopy results including the 2D peak left-shifting and blunting were consistent with those observed in typical n-type doping of graphene.…”
Section: ■ Introductionmentioning
confidence: 94%
“…Both of these Raman spectroscopy results including the 2D peak left-shifting and blunting were consistent with those observed in typical n-type doping of graphene. 19,20,23 Notice that the 2D peak shifted up from 2685 to 2689 cm −1 , while the fwhm values of the 2D peak shifted down from 47 to 45 cm −1 after the n-type doped graphene was treated with RTA at 800°C…”
Section: ■ Introductionmentioning
confidence: 99%
“…a) Mobility of pristine graphene, substitutional‐doped graphene (SDG), covalent‐doped graphene (CDG), graphene nanoribbon (GNR), and noncovalent‐doped graphene . b) E F shift of graphene (Δ E F , marked by circles) after SCTD by various surface dopants and their corresponding energy levels (marked by stars) .…”
Section: Sctd In 2d Nanostructuresmentioning
confidence: 99%
“…[1][2][3][4][5][6] Regarding the electrical property, the carrier transport in 2D materials is very sensitive to the presence of extrinsic adsorbents, which typically cause charged-impurity scattering, charge trapping, and recombination centers, [7][8][9][10][11] leading to degradation of the transport characteristics. [12][13][14] Although various encapsulation methods have been developed, [15][16][17][18][19] it is intriguing to explore methods to control the transport properties in the circumstance of no encapsulated layer. Here, we demonstrated that the short-circuit photocurrent enabled by the built-in electric field at the MoS2 junction is surprisingly insensitive to the gaseous environment, which is very uncommon in the photoresponse of thin transition-metal dichalcogenides (TMDCs).…”
Section: Introductionmentioning
confidence: 99%